ECONOMY AND SOCIAL POLICY IN KARAKALPAKSTAN: EXPERIENCE OF 1950-1960 - Abdukarimov, A.A. (SCIENCE and SOCIETY, 2026)
The article examines the socio-economic processes in Karakalpakstan during the 1950s-1960s. Based on archival documents, statistical data, and memoir sources, it explores the state’s social policy and its impact on the rural population of the republic. Special attention is given to the post-war recovery of the national economy, the development of industry and agriculture, as well as the implementation of social programs in education, healthcare, housing construction, and infrastructure. The study also highlights the contradictions and difficulties caused by voluntarism and subjectivism in governance, as well as restrictions imposed on collective farmers. The research emphasizes the significance of post-war transformations in shaping the social structure of Karakalpakstan and reveals both achievements and challenges of the period under review.
Keywords: Karakalpakstan; social policy; rural population; economy; post-war recovery; 1950s-1960s; education; healthcare; agriculture